Pengaruh Religiusitas terhadap Boycott Intention: Peran Mediasi Brand Attitude dan Moderasi Brand Loyalty. - Devia Putri; Kussudyarsana, Kussudyarsana,; Moechammad Nasir (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of religiosity on consumers’ boycott intention by considering the mediating role of brand attitude and the moderating role of brand loyalty. In the context of increasing awareness of moral and religious values, religiosity is viewed as an important factor shaping consumers’ attitudes and consumption behaviors toward brands perceived to be affiliated with certain ethical and political issues, particularly the genocide committed by Israel against the Palestinian population. This research adopts a quantitative approach using a survey method and is analyzed through Structural Equation Modeling (SEM). The results indicate that religiosity has a positive and significant effect on brand attitude, brand attitude has a positive and significant effect on boycott intention, and brand attitude plays a significant mediating role in the relationship between religiosity and boycott intention. However, brand loyalty does not moderate the relationship between religiosity and boycott intention. These findings provide theoretical implications by contributing to the body of scholarly work in the field of brand marketing management, particularly in understanding how religious, ethical, and social values influence consumer behavior. Practically, this study offers important insights for consumers to support and empower non-affiliated local products, as well as for Indonesian business practitioners to enhance industrial competitiveness, especially in sectors that are still largely dominated by foreign brands affiliated with Israel.